2019
DOI: 10.1111/acer.14154
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Persistent Neurobiological Changes Following Adolescent Alcohol Exposure: NADIA Consortium Findings

Abstract: The Neurobiology of Adolescent Drinking in Adulthood (NADIA) Consortium has focused on the impact of adolescent binge drinking on brain development, particularly on effects that persist into adulthood. Adolescent binge drinking is common, and while many factors contribute to human brain development and alcohol use during adolescence, animal models are critical for understanding the specific consequences of alcohol exposure during this developmental period and the underlying mechanisms. Using adolescent intermi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
162
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 133 publications
(165 citation statements)
references
References 145 publications
(263 reference statements)
3
162
0
Order By: Relevance
“…Alcohol use and binge drinking among adolescents are associated with increased health risks (Miller et al, ), and enhanced propensity for the development of alcohol use disorders (AUDs) in later life (Dawson et al, ; Ehlers et al, ; Hingson et al, ; Johnston et al, ). Adolescence is a critical period for the onset of binge drinking, and alcohol exposure during this time has been demonstrated to produce persistent alterations in neural development, behavior, and drinking levels in adulthood in several rodent models (Alaux‐Cantin et al, ; Crews et al, ; Crews et al, ; Maldonado‐Devincci et al, ; Spear, ; Spear, ; Spear and Swartzwelder, ).…”
mentioning
confidence: 99%
“…Alcohol use and binge drinking among adolescents are associated with increased health risks (Miller et al, ), and enhanced propensity for the development of alcohol use disorders (AUDs) in later life (Dawson et al, ; Ehlers et al, ; Hingson et al, ; Johnston et al, ). Adolescence is a critical period for the onset of binge drinking, and alcohol exposure during this time has been demonstrated to produce persistent alterations in neural development, behavior, and drinking levels in adulthood in several rodent models (Alaux‐Cantin et al, ; Crews et al, ; Crews et al, ; Maldonado‐Devincci et al, ; Spear, ; Spear, ; Spear and Swartzwelder, ).…”
mentioning
confidence: 99%
“…In previous rodent studies, the impact of adolescent intermittent ethanol (AIE) exposure on adult drinking patterns and behaviors has varied. AIE has regularly been shown to increase alcohol drinking, social anxiety, and loss of behavioral flexibility in adulthood in rats (Crews et al 2019;Gilpin, ALCOHOL, ADOLESCENCE, SEX DIFFERENCES, CONSUMPTION 5 Karanikas, and Richardson 2012; Maldonado-Devincci et al 2010;Maldonado-Devincci, Badanich, and Kirstein 2010), while others have found no change in alcohol consumption following adolescent ethanol exposure (Nentwig et al, 2019;Slawecki and Betancourt, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Several models of AIE exposure have been used in both rats and mice, including voluntary consumption in geneticallybred mouse and rat strains, forced gavage exposure, intermittent intraperitoneal injections, forced ethanol consumption with only one bottle of ethanol presented, drinking in the dark, etc. (Acheson et al, 2013;Crews et al, 2019;Gilpin et al, 2012;Maldonado-Devincci et al, 2010a;Miller et al, 2017;Slawecki and Betancourt, 2002;Thiele and Navarro, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Adolescent alcohol exposure can disrupt this normal remodeling of cortical and limbic regions (Spear, ). Replicable effects of adolescent alcohol consumption on the adult brain include a hyperdopaminergic response to stimuli, reduction in choline acetyltransferase (ChAT), alterations in neuroimmune function, and nonspecific modulation of epigenetic factors (Crews et al., ; Mulholland et al., ; Spear and Swartzwelder, ).…”
mentioning
confidence: 99%
“…The consistent findings that AIE exposure results in persistent reduction in ChAT in multiple brain regions (cf. Crews et al., ) would suggest an up‐regulation in cholinergic receptors to maintain functional homeostasis. Up‐regulation of cholinergic receptors would enhance the propensity of DA neurons to respond to EtOH and other drugs of abuse that act on those receptors.…”
mentioning
confidence: 99%